VARIASI BAHASA BERDASARKAN STRATAFIKASI SOSIAL DI DESA MABBIRING KECAMATAN SIBULUE KABUPATEN BONE KAJIAN SOSIOLINGUISTIK - Wandy, Rizwandy; Muhammad Idris; Irna Fitriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the language variation based on social stratification in Mabbiring Village, Sibulue District, Bone Regency, viewed from the economic level. Data were obtained from 81 daily conversations divided into three economic categories: low, middle, and high. The research method used is descriptive qualitative with participatory observation, interview, documentation, and recording techniques. The results show differences in language variation in four main aspects: lexical choice, sentence structure, speech style, and formality level. The low economic group tends to use local and concrete vocabulary, simple sentence structures, and casual speech styles. The middle economic group uses more varied forms both lexically and syntactically with a moderate level of formality, while the high economic group demonstrates a more formal, structured, and symbolic variety. Factors influencing language variation include education level, occupation, social environment, language habits, and cross-strata interaction intensity. Keywords: Language variation, social stratification, economy, sociolinguistics, Bugis culture ABSTRAK Penelitian ini b